Evaluation of the Impact of Implementing Electronic Prescription in an Oncology Referral Hospital in Recife, Brazil - Diana Carla Gouveia Falcão; Ana Lara Vieira Soares; Hermes Castro de Araujo-Junior; José Kilderlan Nascimento de Souza-Filho; Natália Moura Farias de Medeiros; Paulo Victor Brasileiro Mota; Rodolfo Basílio Madeira-Neto; Tiago Costa Maia; Marcio Roberto Pinho Pereira; Maria Angelina Silva Medeiros (Brazilian Journal of Oncology)
Introduction The occurrence of errors in the prescription of antineoplastic oncological drugs constitutes a serious public health problem, directly affecting patient safety. In Brazil, the Protocol for the Safety in Prescription, Use, and Administration of Medications, established in 2013, aims to improve care related to medication use in healthcare facilities. This study aims to evaluate the prescription profiles of patients undergoing antineoplastic chemotherapy treatment admitted to the Pernambuco Cancer Hospital before and after the implementation of electronic prescription.